Agroeconomic study of cassava in Sub-Saharan Africa - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
A proposal is presented to carry out an agroeconomic study of cassava in Sub-Saharan Africa, which will provide an in-depth characterization of cassava production, processing, and marketing. Aspects covered will be the structure of cassava-based cropping systems in principal and potential producing areas, the technical and economical parameters for traditional cassava processing techniques, estimates of consumption of cassava products, role of cassava as a source of income and structure of marketing channels, demand parameters for different cassava products in urban areas, and impact of price and import policies for grains on the production and consumption of cassava. Project structure, research methodology, topic and area coverages, time frame, and financial requirements are indicated. Potential collaborators (national research institutes and universities) are listed for priority countries. Background information is also given on the role of cassava within the context of the African food situtation, development strategies for the crop (increased productivity, movement into marginal areas, expanding urban demand), and present status of cassava research within the CGIAR system. (CIAT)